Mass Propagation of Antagonistic Bacteria Pseudomonas fluorescens as an Environmental-Friendly Biocontrol Agent - Yosua Nathanael Itona Sagala; Ramadhani Mahendra Kusuma; Suharto (Future Science, 2022)
Biological control is a long-term and environmentally friendly method of pest management. The use of biological control agents has several advantages. These advantages include limiting the growth and development of plant-disrupting organisms over a relatively long period. Furthermore, biological agents have advantages in maintaining the equilibrium of the ecosystem that is present in agricultural environments. Due to their ability to create antimicrobials and stimulate plant development, as well as the fact that they are plant growth-promoting rhizobacteria (PGPR) and can survive in adverse environmental circumstances, antagonistic bacteria are one of the biological or biocontrol agents for managing illness. Antagonizing microorganisms can boost plant resilience to disease attack without polluting the environment or leaving toxic residues in the food chain Bacteria with good antagonistic agent properties can prevent the growth of pathogens and stimulate plant resistance responses. In addition, antagonistic bacteria can simultaneously boost the growth response of plants (plant growth promoter). One of the antagonistic bacteria used as PPGF is Pseudomonas fluorescens. Pseudomonas fluorescens has been widely recognized as having the potential as a biological agent to inhibit several plant pathogens. P. fluorescensis a group of root bacteria that effectively suppresses various plant diseases, including damping off of seedlings, soft rot, bacterial wilt, and others on many plant varieties. An antibiotic substance produced by P. fluorescens. (2,4-diacetylphloroglucinol/ 2,4-DAPG) can increase soil resistance to pathogens.